"Falsehood and Fallacies": Brandeis, Free Speech and Trumpism. Issue 2 (3rd April 2017) - Russomanno, Joseph
Abstract : Donald Trump's campaign for the presidency in 2016 was unique, noted for a number of attributes that rarely, if ever, had been witnessed, including the candidate's propensity to freely express his views, unfiltered. Debates surfaced, including some within his own party and campaign team, whether to let Trump be Trump. In other words, there was controversy as to whether he should continue to speak freely while campaigning, or if his speech should be restricted, with him staying on script and on message. The free speech philosophy of Justice Louis Brandeis, which includes exposing "falsehood and fallacies" with more speech, is an ideal theoretical perspective to apply. By juxtaposing the pillars of Brandeis' philosophy – fear, civic courage, education and democracy – with Trump's campaign approach, this article demonstrates the efficacy of this application, but not without also focusing on Brandeis' emphasis on education, civic awareness and confronting the danger of an inert people.